The Artist’s Film Portrait in the Film Martiros Saryan (1965) by L. Vagharshyan: Facets of the Image - Voskresenskaya Victoria V. (Художественная культура)
The article examines the specifics of the artist’s film portrait dedicated to the 85th anniversary of the master and created at the Armenfilm studio in 1965 (director — Laert Vagharshyan, scriptwriters — Laert Vagharshyan and Ilya Ehrenburg, cameraman — Marat Varzhapetyan, composer — Lazar Saryan). The film is analyzed in connection with sociocultural, artistic, ideological aspects of the comprehension and implementation of the artist’s creative work and image in the late Thaw period in a non-fiction film. The film openly draws attention to the tragic pages of M.S. Saryan’s (1880– 1972) creative biography: the 1937 destruction of his portraits of a number of repressed Armenian political and cultural figures, his reaction to accusations of formalism. The film, which was not widely distributed, is an extraordinary example of creating an image of a man of art in Soviet documentary cinema. In addition to the film material, the study is based on the director’s memoirs, the contemporaries’ reviews and film criticism relevant for that time.